Prevention of Influenza Hospitalization Among Adults in the United States, 2015–2016: Results From the US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN). (14th December 2018) - Ferdinands, Jill M; Gaglani, Manjusha; Martin, Emily T; Middleton, Don; Monto, Arnold S; Murthy, Kempapura; Silveira, Fernanda P; Talbot, H Keipp; Zimmerman, Richard; Alyanak, Elif; Strickland, Courtney; Spencer, Sarah; et al.
Abstract: Background: Evidence establishing effectiveness of influenza vaccination for prevention of severe illness is limited. The US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN) is a multiyear test-negative case-control study initiated in 2015–2016 to estimate effectiveness of vaccine in preventing influenza hospitalization among adults. Methods: Adults aged ≥18 years admitted to 8 US hospitals with acute respiratory illness and testing positive for influenza by polymerase chain reaction were cases; those testing negative were controls. Vaccine effectiveness was estimated with logistic regression adjusting for age, comorbidities, and other confounding factors and stratified by frailty, 2-year vaccination history, and clinical presentation. Results: We analyzed data from 236 cases and 1231 controls; mean age was 58 years. More than 90% of patients had ≥1 comorbidity elevating risk of influenza complications. Fifty percent of cases and 70% of controls were vaccinated. Vaccination was 51% (95% confidence interval [CI], 29%–65%) and 53% (95% CI, 11%–76%) effective in preventing hospitalization due to influenza A(H1N1)pdm09 and influenza B virus infection, respectively. Vaccine was protective for all age groups. Conclusions: During the 2015–2016 US influenza A(H1N1)pdm09–predominant season, we found that vaccination halved the risk of influenza-association hospitalization among adults, most of whom were at increased risk of serious influenza complications due to comorbidity or age. Abstract : During the 2015–2016 US influenza A(H1N1)pdm09–predominant season, we found that vaccination halved the risk of influenza-association hospitalization among adults, most of whom were at increased risk of serious influenza complications due to comorbidity or age.